Introdução ao estudo da Álgebra para alunos do ensino fundamental - Kucinskas, Ricardo (Universidade Federal de São Carlos, 2017)
This dissertation of professional masters proposes the introduction of the Algebra study for elementary school students. Our main objective was to develop a work outlined in didactic sequence, based on instigating problems that would challenge the independent thinking, essential for the effectiveness of the meaningful learning. For this purpose, a didactic sequence will be presented by three phases: Algebraic Thinking, Algebraic Expressions and First Degree Equations. In order to develop algebraic thinking, students were mobilized to study models and regularities. After that, problems that explored the variation of quantities and the generalization of patterns led them to read and represent some algebraic expressions as well as to calculate its numeric value in various contexts. Finally, our intention was to translate situations through first degree equations, analyzing them, finding their respective roots and validating the results found. As for the development of this research and the data analysis, we were guided by a qualitative approach, since the interactive contact of the researcher as a teacher at a municipal school provided the construction of a reality of students inserted in a particular universe of beliefs, values and several meanings. As the most important result, we realized that 7th grade students initially had only intuitive conceptual notions and had some difficulty in dealing with algebraic calculations. Therefore, problem solving proved to be an effective methodology for students to appropriate Algebra as a meaningful knowledge.
Keywords: Pensamento algébrico; Expressões algébricas; Equação do primeiro grau; Sequência didática; Aprendizagem significativa; Resolução de problemas; Algebraic thinking; Algebraic expressions; First degree equations; Didactic sequence; Meaningful learning; Problem solving; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM